SITUS INVERSUS TOTALIS IN A NEWBORN WITH CONGENITAL HEART DISEASE - Stomnaroska Damchevski, Orhideja; Jancevska, Aleksandra; Ristovska, Sanja (Македонско лекарско друштво = Macedonian medical association, 2024)
Introduction. Situs inversus totalis (SIT) is rarely re- ported in newborns. Isolated or associated with other congenital abnormalities, most often with congenital heart malformations (3-9%), SIT can often be an acci- dental finding. Case report. We report a term-newborn with SIT and complex congenital heart defect, diagnosed prenatally by fetal ultrasound. SIT was confirmed with plane film X-ray (liver on a left side, spleen on right side). Heart ultrasound was done and revealed a complex cardiac malformation (CHM) - dextrocardia, single ventricle, tricuspidal valvular atresia, hypoplastic aortae, ASD II, PDA. The baby was transferred to a heart surgery center where the neonate was treated but unfortunately pa- ssed away. Conclusion. SIT with CHM is a rare condition in neonatal period. Although a myriad of congenital malformations can be accompanying, isolated SIT is the most common. SIT and CHM is a condition challenging for surgical treatment.
SITUS INVERSUS TOTALIS КАЈ НОВРОДЕНЧЕ СО КОНГЕНИТАЛНА СРЦЕВА МАЛФОРМАЦИЈА